PENGARUH CORPORATE SOCIAL RESPONSIBILITY (CSR) TERHADAP KINERJA KEUANGAN PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA (BEI) TAHUN 2018-2019 - Nur Oktamayuni (Program Studi Manajemen Keuangan Syariah, 2021)
This thesis aims to determine the effect of Corporate Social Responsibility (CSR) on the financial performance of manufacturing companies listed on the Indonesia Stock Exchange (IDX). In this study, the financial performance of manufacturing companies is measured by Return On Assets (ROA) and Return On Equity (ROE). Corporate Social Responsibility (CSR) as an independent variable and Return On Assets (ROA) and Return On Equity (ROE) as dependent variables. The sample in this study is a manufacturing company listed on the Indonesia Stock Exchange (IDX) in 2018-2019. The data was collected using the literature study method. With the results obtained as many as 68 manufacturing companies listed on the Indonesia Stock Exchange (IDX). This research uses panel data regression analysis with Fixed Effect model selection. The results show that Corporate Social Responsibility (CSR) on the financial performance of manufacturing companies listed on the Indonesia Stock Exchange (IDX) in 2018-2019 has a significant effect on the company's financial performance as measured by Return On Assets (ROA) and Return On Equity (ROE). ).